2006
DOI: 10.1016/j.theriogenology.2006.02.016
|View full text |Cite
|
Sign up to set email alerts
|

Heparin-binding proteins of canine seminal plasma

Abstract: Heparin-binding proteins (HBP) from seminal plasma have been expected to participate in modulation of the acrosomal reaction, and have been correlated with fertility in some species. However, they have not been described in the dog. The aim of this study was to document the HBPs of canine seminal plasma. Six pooled samples of seminal plasma from three crossbred dogs were used. The HBPs were isolated by heparin affinity chromatography and the fractions recovered were pooled. One-dimensional sodium dodecyl sulph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
13
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 16 publications
2
13
0
Order By: Relevance
“…Arginine esterase, also known as canine prostate specifi c protein (CPSE) is a protein with enzymatic activity that is found in high concentrations in the canine prostatic fl uid and has been associated with fertility (MCENTEE et al, 1987;SOUZA et al, 2006). Previous reports suggested that the 15kDa band may be a subunit of the arginine esterase (SOUZA, 2003).…”
Section: Resultsmentioning
confidence: 99%
“…Arginine esterase, also known as canine prostate specifi c protein (CPSE) is a protein with enzymatic activity that is found in high concentrations in the canine prostatic fl uid and has been associated with fertility (MCENTEE et al, 1987;SOUZA et al, 2006). Previous reports suggested that the 15kDa band may be a subunit of the arginine esterase (SOUZA, 2003).…”
Section: Resultsmentioning
confidence: 99%
“…These proteins appear to participate in the bovine sperm membrane lipid modifications that occur during Capacitation [39] . De Souza and coworkers [28] reported that the proteins resembling BSP were found in crossbred dog seminal plasma (58.6, 67 and 61.5 kDa). However, these investigators did not show whether these proteins were present in all fractions of the ejaculates or if they were only found in prostatic fluid.…”
Section: Discussionmentioning
confidence: 99%
“…Boisvert et al [27] also isolated and characterized homologous proteins from bison seminal vesicle secretion (BiSV-16, BiSV-17, BiSV-18 and BiSV-28 kDa). Furthermore, De Souza et al [28] identified these heparin-binding proteins, particularly the 61.5 kDa protein, in the prostate secretions of 3 crossbred dogs and investigated whether these proteins were involved in the acrosome reaction of sperm. Cross [2] reported that prostasomes that are expelled from the prostate gland at ejaculation contain large amounts of cholestero and the fusion between prostasomes and sperm enriches the sperm membrane in cholesterol, thereby delaying the acrosome reaction and decreasing membrane fluidity [1,3,29] .…”
Section: Introductionmentioning
confidence: 99%
“…HBPs bind to the spermatozoa surface after ejaculation and affect fertility due to their modulatory role during the acrosome reaction (MANJUNATH et al, 1993). SOUZA et al (2006), using heparin affinity chromatography followed by one-dimensional electrophoresis (12% and 18% SDS-PAGE), reported that 19 protein bands of the canine SP bound to the heparin column. Of these 19 proteins, a 61.5kDa protein was particularly thought be involved in the canine acrosome reaction (SOUZA et al, 2006).…”
Section: Proteins Of the Canine Spmentioning
confidence: 99%